Early mucosal sensing of SIV infection by paneth cells induces IL-1β production and initiates gut epithelial disruption. - Lauren A Hirao; Irina Grishina; Olivier Bourry; William K Hu; Monsicha Somrit; Sumathi Sankaran-Walters; Chris A Gaulke; Anne N Fenton; Jay A Li; Robert W Crawford; Frank Chuang; Ross Tarara; et al. (PLoS Pathogens)
HIV causes rapid CD4+ T cell depletion in the gut mucosa, resulting in immune deficiency and defects in the intestinal epithelial barrier. Breakdown in gut barrier integrity is linked to chronic inflammation and disease progression. However, the early effects of HIV on the gut epithelium, prior to the CD4+ T cell depletion, are not known. Further, the impact of early viral infection on mucosal responses to pathogenic and commensal microbes has not been investigated. We utilized the SIV model of AIDS to assess the earliest host-virus interactions and mechanisms of inflammation and dysfunction in the gut, prior to CD4+ T cell depletion. An intestinal loop model was used to interrogate the effects of SIV infection on gut mucosal immune sensing and response to pathogens and commensal bacteria in vivo. At 2.5 days post-SIV infection, low viral loads were detected in peripheral blood and gut mucosa without CD4+ T cell loss. However, immunohistological analysis revealed the disruption of the gut epithelium manifested by decreased expression and mislocalization of tight junction proteins. Correlating with epithelial disruption was a significant induction of IL-1β expression by Paneth cells, which were in close proximity to SIV-infected cells in the intestinal crypts. The IL-1β response preceded the induction of the antiviral interferon response. Despite the disruption of the gut epithelium, no aberrant responses to pathogenic or commensal bacteria were observed. In fact, inoculation of commensal Lactobacillus plantarum in intestinal loops led to rapid anti-inflammatory response and epithelial tight junction repair in SIV infected macaques. Thus, intestinal Paneth cells are the earliest responders to viral infection and induce gut inflammation through IL-1β signaling. Reversal of the IL-1β induced gut epithelial damage by Lactobacillus plantarum suggests synergistic host-commensal interactions during early viral infection and identify these mechanisms as potential targets for therapeutic intervention.